Metabolomics Study of Guizhi Fuling Capsules in Rats With Cold Coagulation Dysmenorrhea - Zhang, Yu; Su, Na; Liu, Weiyi; Wang, Qingqing; Sun, Jianguo; Peng, Ying (Frontiers in Pharmacology, 2021)
Dysmenorrhea refers to a kind of uterine cramping pain that occurs in women during the period of menstrual. Guizhi Fuling Capsules are mainly used for the treatment of various pain syndromes and especially effective in treating primary dysmenorrhea. However, the research on its modern pharmacology and mechanism of action have not been thoroughly carried out. It is not clear about the main active ingredients, potential targets and metabolic pathways involved in its efficacy. Therefore, this research project employed estradiol benzoate sensitization combined with oxytocin pain to construct the cold coagulation syndrome dysmenorrhea model, observed the anti-dysmenorrhea effect of Guizhi Fuling Capsules, and used the metabolomics to explore its mechanism. The results showed that Guizhi Fuling Capsules could considerably reduce the number of writhing times in dysmenorrhea rats, increasing the level of PGE2 and β-EP and reducing the contents of PGF2α in rat serum. Pathological sections of uterus and ovaries also showed that Guizhi Fuling Capsules could significantly relieve endometrial hyperplasia and improve ovarian function. The LC/MS-based metabolomics of rat uterine indicated that the model group has a great deviation from the control group. Compared with the model group, the Guizhi Fuling Capsules group had a tendency to shift to the control group, and the main metabolic changes was mainly concentrated on saturated and unsaturated fatty acids. Among them, arachidonic acid is in a pivotal position, and the expression of its rate-limiting enzyme (COX-2) involved in its cyclooxygenase metabolic pathway was significantly up-regulated in the model group, but significantly decreased after the intervention of Guizhi Fuling Capsules. In conclusion, Guizhi Fuling Capsules can effectively relieve primary dysmenorrhea, and this effect may be attributed to the regulation effects of Guizhi Fuling Capsules on endogenous metabolism, such as inhibiting arachidonic acid converted to prostaglandins through downregulate the expression of COX-2, which plays an anti-inflammatory effect.